2020
DOI: 10.17221/125/2020-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three kinds of protease on growth performance, apparent digestibility of nutrients and caecal microbial counts in weanling pigs

Abstract: This experiment investigated the effects of three single kinds of protease on performance, serum parameters, apparent digestibility of nutrients and caecal microorganisms in weanling pigs. One hundred and ninety-two White × Landrace × Duroc hybrid pigs (7.51 ± 0.81 kg) were allotted to 1 of 4 treatments for 28 days. No protease was added to the control diet and the three experimental diets were supplemented with the same proportion of 10 IU/kg of alkaline, acidic and neutral protease, respectively. The supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The protease supplementation of the pigs’ diet resulted in a comparable performance as in the group fed with the diet without the enzyme, but FCR was higher. Similarly, Hanczakowska and Świątkiewicz et al [ 21 ] and Ma et al [ 49 ] found that although protease supplementation could improve the average daily weight gain, it did not have positive influence on the FI and FCR when the diet contained processed or unprocessed legume seeds. On the contrary, Zuo et al [ 14 ] found that higher dietary protease supplementation increased the growth performance of pigs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The protease supplementation of the pigs’ diet resulted in a comparable performance as in the group fed with the diet without the enzyme, but FCR was higher. Similarly, Hanczakowska and Świątkiewicz et al [ 21 ] and Ma et al [ 49 ] found that although protease supplementation could improve the average daily weight gain, it did not have positive influence on the FI and FCR when the diet contained processed or unprocessed legume seeds. On the contrary, Zuo et al [ 14 ] found that higher dietary protease supplementation increased the growth performance of pigs.…”
Section: Discussionmentioning
confidence: 97%
“…Zuo et al [ 14 ] found that protease supplementation at a dose of 200 and 300 mg/kg, but not at 100 mg per kg of the diet, improved the digestibility of crude protein but did not improve the digestibility of dry matter. Ma et al [ 49 ] found increased apparent digestibility coefficients of crude protein in the pigs which received dietary supplementation with ‘alkaline’ or ‘acidic’ protease but not ‘neutral’ ones. Zuo et al [ 14 ] observed that the supplementation of a diet containing unprocessed seeds with an enzyme additive improved the morphometric parameters of the ileum and the activity of pepsin, amylase, and trypsin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaline exogenous proteases have an optimum activity when pH is close to the alkaline range (Cowieson and Ross, 2016;Ma et al, 2020). Thus, they have greater hydrolysis activity in the small intestine (Cowieson and Ross, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…During the late laying period, the secretion ability of endogenous enzymes is weakened and resulted of the decrease in the digestibility of laying hens and then leading to the reduction of egg production (Usman et al, 2014). In the previous studies, the dietary supplementation of protease could enhance the endogenous enzymes hydrolysis ability and improve broiler performance (Barekatain et al, 2013;Freitas et al, 2011) and also increase the amino acid digestibility of weaned and growing pigs fed with corn-soy diets (Ma et al, 2020;Pan et al, 2016;Yu et al, 2016). However, only a few reports focused on AKP supplementation for laying hens, particularly its effect on the intestinal microbiota in late laying period.…”
mentioning
confidence: 99%